PENGARUH INJEKSI AIR DAN PENGATURAN DERAJAT PENGAPIAN TERHADAP PENURUNAN KONSUMSI BAHAN BAKAR MESIN SEPEDA MOTOR - Myson Myson (Universitas Batanghari, 2017)
Water injection is a hydraulic technique of injecting water into the combustion chamber with the purpose to decrease the amount of fuel sipped by pistons during the expansion, and replaced it with water directly injected to combustion chamber. This water injection process also reduce temperature in combustion chamber . Besides degree of ignition is having a significant effect on quality of combustion earning. Angle of earlier ignition will cause increase of combustion pressure speed, which in turn makes pressure result of combustion in excelsior cylinder. But if degree of ignition in backs into, hence time required by fuel for combustible become smaller and fuel can be combustible at outlet. Result from test conducted by moving forward degree of ignition and water injection done at honda mega- pro and honda supra fit showed that efficiency of engine can be improved. For motorbike Honda Mega- Pro result showed improved of specific fuel consumtion to torsion equal to 47,82% with treatment of water injection mixed with alcohol with ratio 60:40 at degree of ignition moved forward by 3 degree of at burden 1 KW (Kilo Watt). For Honda Supra Fit improved of specific fuel consumtion to torsion 25,14 % at treatment of water injection mixed with by alcohol at ratio 80:20 with degree of ignition is moved forward 5 degree of at burden 1 KW.Keyword : Water injection, degree of ignition, improved efficiency, motorcycle engine